Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Étude exploratoire de la sexualisation féminine telle que vécue par des adolescentes à l'intérieur des relations hétérosexuelles - Grisé, Elaine (Université du Québec à Montréal, 1996)
Keywords: 1900-1999; 1990-1999; IREF; adolescentes*; discipline; hétérosexualité; identité sexuelle; mémoires/thèses; périodes historiques; sciences humaines; sexologie

Sexualité et séropositivité : représentations sociales de femmes séropositives au virus de l'immunodéficience humaine (VIH) - Mensah, Maria Nengeh (Université du Québec à Montréal, 1994)
Keywords: 1900-1999; 1990-1999; IREF; VIH; discipline; mémoires/thèses; périodes historiques; santé; sciences humaines; sexologie; sexualité; thématiques